Hubungan Tekanan Darah Dengan Pernafasan Bayi Baru Lahir - Mariah Ulfah (Universitas Harapan Bangsa Purwokerto, 2016)
The physiological changes that occur in neonates heaviest is the transmission of the placentainto the fetal circulation or respiration independently. Factors affecting the normaltransmission of this or that increases asphyxia (state hypoxemia, hypercapnia, and acidosis)fetus will affect the adjustment of the fetus to life extrauterine Interference in breathing canoccur there is a new baby is born, one of which is caused by a factor mother of them arerelated with blood pressure is hypotension or preeclampsia (Masyita Dea, 2014) Based onthe pre-survey conducted on February 1 until March 4, 2016 in General Hospital Cilacapshows there are 221 maternal, from record data medic there were nearly 9.95% of maternaldisease associated with blood pressure that is consecutive gestational hypertension 6 cases,severe preeclampsia 12 cases, 4 cases mild pre-eclampsia, and even two cases of HELLPsyndrome to be at risk of neonatal respiratory disorders (RM Hospital Cilacap, 2016) Objective of the research are : 1) Determine the incidence of maternal blood pressure inCilacap General Hospital in 2016. 2) Determine the incidence of respiratory Newborn inHospital Cilacap 2016. 3) Knowing Relations maternal blood pressure Systole withrespiratory Newborn in Hospital Cilacap year 2016. 4) Knowing Relations diastolic bloodpressure with respiratory maternal Newborn in Cilacap General Hospital in 2016. This studywas an crossectional method and data were analyzed using Chi-square test The results showed 1) The highest maternal age in healthy reproductive age range (20-35) is71.3% compared to the age of> 35 years of 20.7% and <20 years at 8%. 2) characteristics ofrespondents based on parity tertinggiadalah primipara (77.0%) compared with multiparous(17.2%) and Grandemultipara (5.7%) 3) The state of maternal systolic that systolic bloodpressure <140 mmHg 85% higher than the systolic blood pressure of 140-159 mmHg 11.5%,systolic blood pressure>: 160 mm Hg was 3.4%. 4) The state of maternal bahwatekanandiastolic diastolic <90,, Hg is the highest compared to 69.5% diastolic blood pressure of 90- 109 mm Hg (29.3%), and> 110 mmHg (1.1%). 5) The state of the newborn breathingregularly higher (58.6%) compared to the irregular breath (41.4%). 6) There is a relationshipof systolic blood pressure with respiratory newborns Keyword: heart failure, respiratory newborn baby, labour